Predicting Potential Fishing Zones of Large Pelagic Fish in Mamuju Regency Waters - Safruddin, 1; Mukti Zainuddin, 2; Chair Rani, 3 (Journal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2014)
Large pelagic species such as tuna are known to be abundant in Mamuju Waters, Makassar Strait. Â The distribution and abundance of the fish in that area are expected to be related to the distributions of sea surface temperature and chlorophyll-a concentration. This study aims to predict spatial and temporal distribution of the species during the period of June 2013-May 2014. Â Probability indices used for detection of tuna potential fishing zones (PFZs) were constructed from a model of satellite-based SST and chlorophyll data in relation to tuna fishery. Results showed that the occurrence of tuna species in Mamuju Water were mostly predicted in areas of 118Â°12â-118Â°48â E 1Â°48â â 2Â°30âS with the total area of approximately 7,495 km2.Â  Â The potential fishing zones were mainly found in August. Â It was likely that tuna potential fishing zones associated with the preferred oceanographic factors throughout the study area.